Streamer Attributes and Impulsive Buying Behavior: The Mediating Role of Customer Engagement in TikTok Shop Live Streaming Commerce - Hendri Triyanto; Budhi Haryanto (CV. Creative Tugu Pena, 2026)
The development of live streaming commerce has changed the way consumers interact with digital platforms and make online purchasing decisions. Platforms like TikTok, through their TikTok Shop feature, combine entertainment, social interaction, and real-time product promotions, which can encourage impulsive buying behavior. However, not all viewers who watch live streaming sessions make purchases, so it is important to understand the psychological mechanisms that influence consumer engagement and purchasing decisions in this context. This study aims to analyze the influence of streamer attributes, including positive emotion, streamer credibility, and streamer interaction quality, on impulsive buying behavior through customer engagement as a mediating variable. This research framework is based on Stimulus–Organism–Response Theory, which explains that environmental stimuli can influence an individual's psychological state before producing a specific behavioral response. This study uses a quantitative approach with data collection through a survey of 390 respondents who have experience watching live streaming commerce on TikTok Shop. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results show that positive emotion, streamer credibility, and streamer interaction quality have a positive and significant effect on customer engagement. Furthermore, customer engagement was shown to have a significant positive influence on impulsive buying behavior and acted as a mediating variable in the relationship between streamer attributes and impulsive buying behavior. These findings suggest that consumer engagement is a crucial psychological mechanism linking live streaming experiences to spontaneous purchasing decisions in live streaming commerce environments.